2016
DOI: 10.1103/physrevb.93.174522
|View full text |Cite
|
Sign up to set email alerts
|

Electron doping evolution of the neutron spin resonance inNaFe1xCoxAs

Abstract: Neutron spin resonance, a collective magnetic excitation coupled to superconductivity, is one of the most prominent features shared by a broad family of unconventional superconductors including copper oxides, iron pnictides, and heavy fermions. In this work, we study the doping evolution of the resonances in NaFe1−xCoxAs covering the entire superconducting dome. For the underdoped compositions, two resonance modes coexist. As doping increases, the low-energy resonance gradually loses its spectral weight to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Using polarized neutron scattering, it was further found that the mode at lower energy is anisotropic in spin space while the one at higher energy is isotropic [42]. With increasing doping the low-energy mode gradually loses spectral weight, while the mode at higher energy is present across the superconducting dome [20]; however it is unclear how doping affects spin fluctuations in terms of spin anisotropy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using polarized neutron scattering, it was further found that the mode at lower energy is anisotropic in spin space while the one at higher energy is isotropic [42]. With increasing doping the low-energy mode gradually loses spectral weight, while the mode at higher energy is present across the superconducting dome [20]; however it is unclear how doping affects spin fluctuations in terms of spin anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…The energy of the resonance mode (E r ) well inside the superconducting state has been proposed to universally scale with either the superconducting transition temperature T c (E r ≈ 4-6 k B T c ) [16,17] or the superconducting gap 2 (E r ≈ 0.64 × 2 ) [18], although some iron-based superconductors deviate from such scalings [19][20][21][22]. The energy of the resonance mode was also found to track the superconducting order parameter as a function of temperature in optimally electron-doped BaFe 1.85 Co 0.15 As 2 [23].…”
Section: Introductionmentioning
confidence: 99%
“…In electron-doped NaFe 1−x Co x As, two resonance modes are seen in underdoped compositions 24 , with the lower-energy-mode gradually losing spectral weight upon further doping before disappearing near optimal doping 33,34 . The energy of the single resonance mode in well-overdoped NaFe 1−x Co x As does not scale with T c , likely due to multi-orbital physics and impurity effects 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The energy of the single resonance mode in well-overdoped NaFe 1−x Co x As does not scale with T c , likely due to multi-orbital physics and impurity effects 33 . Since superconducting domes are absent in Cu-doped AFe 2 As 2 16,35 , it is unclear if superconductivity induced by Cu-doping has similar electronic and magnetic properties as their electron/holedoped counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly to note that the spin resonance appears below Tc in the superconductors and its energy is related to T c with the well know relation Δ reso~4 .3*T c (for pnictides) and ~5.4*T c (for cuprates) [85,86], while the spin-gap in Kondo insulators appears at a temperature below T χ max and its value is related to T K with relation Δ spin~3 * T χ max = T K [28]. Further a similar resonant mode in the non-superconducting antiferromagnetic heavy-fermion metal CeB 6 has been observed at the Q-position corresponding to antiferro-quadrupolar (AFQ) ordering (½, ½, ½) [87].…”
Section: (B) Hybridization Gap Study In the Kondo Insulator Cefe 2 Al 10mentioning
confidence: 99%